The Initial State of Educating Future Primary School Teachers in a Multilingual Context - Kydyrbayeva, Gulnaz; Makhmetova, Djamilya; Kulzhanbekova, Galiya; Anayatova, Raziyam; Otetileuova, Assel; Tashenova, Zhanat (Aptisi Transactions On Technopreneurship (ATT), 2026)
In multilingual countries, a crucial issue is the preparation of future teachers for instructing in one or several additional languages. Proficiency in at least three languages is considered one of the fundamental educational competencies. This could include the second language of the country, the mastery of which contributes to preserving its cultural and linguistic diversity, as well as one or several foreign languages, such as English, which is widely used in international communication amidst the conditions of globalization. Kazakhstan has implemented a trilingual education policy known as the ‘Trinity of Languages’ initiative. It mandates the use of Kazakh, Russian, and English in schools with the aim of fostering national unity, preserving heritage languages, and enhancing global communication skills among students. The present study is dedicated to exploring the issue of preparing future teachers of natural sciences for instruction in the context of multilinguism. The demand for such teachers is explained by the gradual transition of general education schools in the Republic of Kazakhstan to teaching in three languages Kazakh, Russian and English and studying natural sciences in the primary grades in English. A future educator teaching a subject in a second (or foreign) language should possess well-developed communication skills, be able to independently plan lessons considering both language and subject-specific objectives, and teach while fostering the development of students’ knowledge in the subject, academic English language, and higher-order thinking. The necessity for preparing such professionals underscores the relevance of the conducted research.